Composition and surface optical properties of GaSe: Eu crystals before and after heat treatment [Articol] - Sprincean, Veaceslav; Haoyi, Qiu; Tjardts, Tim; Lupan, Oleg; Untila, Dumitru; Aktas, Oral Cenk; Adelung, Rainer; Leontie, Liviu; Cârlescu, Aurelian; Gurlui, Silviu; Caraman, Mihail (My University, 2024)
This work studies the technological preparation conditions, morphology, structural char- acteristics and elemental composition, and optical and photoluminescent properties of GaSe single crystals and Eu-doped β–Ga2O3 nanoformations on ε–GaSe:Eu single crystal substrate, obtained by heat treatment at 750–900 ◦C, with a duration from 30 min to 12 h, in water vapor-enriched atmosphere, of GaSe plates doped with 0.02–3.00 at. % Eu. The defects on the (0001) surface of GaSe:Eu plates serve as nucleation centers of β–Ga2O3:Eu crystallites. For 0.02 at. % Eu doping, the fundamental absorption edge of GaSe:Eu crystals at room temperature is formed by n = 1 direct excitons, while at 3.00 at. % doping, Eu completely shields the electron–hole bonds. The band gap of nanostructured β–Ga2O3:Eu layer, determined from diffuse reflectance spectra, depends on the dopant concentration and ranges from 4.64 eV to 4.87 eV, for 3.00 and 0.05 at. % doping, respectively. At 0.02 at. % doping level, the PL spectrum of ε–GaSe:Eu single crystals consists of the n = 1 exciton band, together with the impurity band with a maximum intensity at 800 nm. Fabry–Perrot cavities with a width of 9.3 μm are formed in these single crystals, which determine the interference structure of the impurity PL band. At 1.00–3.00 at. % Eu concentrations, the PL spectra of GaSe:Eu single crystals and β–Ga2O3:Eu nanowire/nanolamellae layers are determined by electronic transitions of Eu2+ and Eu3+ ions.
SPRINCEAN, Veaceslav; Haoyi QIU; Tim TJARDTS; Oleg LUPAN; Dumitru UNTILA; Oral Cenk AKTAS; Rainer ADELUNG; Liviu LEONTIE; Aurelian CÂRLESCU; Silviu GURLUI și Mihail CARAMAN. Composition and Surface Optical Properties of GaSe: Eu Crystals before and after Heat Treatment. Materials, 2024. vol. 17, pp. 1-15. ISSN 1996-1944.
Keywords: chalcogenides; gallium(III) trioxide; native oxide; Eu doping; single crystals; layers; optical properties; photoluminescence